Pembuatan sistem pengukuran besaran gerak lurus berbasis personal komputer menggunakan sensor optocoupler - Rani Humaira (PILLAR OF PHYSICS, 2016)
Linier motion experiment is one of important experiment in physics because linear motion is basic motion which learned in the physics. The objective of this research is create a system of measuring linear motion parameters with good accuracy and precision and able to display data and graphics of linier motion parameters on personal computers using five HY860D optocoupler sensors with microcontroller Atmega 328 integrated on Arduino Uno board. There are three results of this research. First, the measurement system design consisting of five optocoupler sensor hang on a sensor pole with spacing between each sensor pole 50 cm, data of linier motion parameters which displayed on a computer include distance, time, average velocity and acceleration from each sensor and graphics show relation between distance and time, average velocity and time, acceleration and time. Second, the percentage of precision of time, average velocity, and acceleration for the measurement of uniform linear motion respectively 99.70 %, 99.91 %, and 100 %, percentage of precision of time, average velocity, and acceleration for the measurement of accelerated linier motion respectively 99.82 % , 86.18 % , and 98.70 %. Third, the average accuracy of time, average velocity and acceleration of uniform linear motion respectively 98.07%, 93.49 %, and 82.12 %, and average accuracy of time, average velocity and acceleration of the uniformly accelerated respectively 97.05 %, 98.22 %, and 90.04 %